Zinc mediates the neuronal activity-dependent anti-apoptotic effect. - Mei Qiu; Yang-Ping Shentu; Ji Zeng; Xiao-Chuan Wang; Xiong Yan; Xin-Wen Zhou; Xiao-Peng Jing; Qun Wang; Heng-Ye Man; Jian-Zhi Wang; Rong Liu (PLoS ONE)
Synaptic activity increases the resistance of neurons to diverse apoptotic insults; however, the underlying mechanisms remain less well understood. Zinc promotes cell survival under varied conditions, but the role of synaptically released zinc in the activity-dependent anti-apoptotic effect is unknown. Using cultured hippocampal slices and primary neurons we show that a typical apoptosis inducer-staurosporine (STP) was able to cause concentration-dependent apoptotic cell death in brain slices; Enhanced synaptic activity by bicuculline (Bic)/4-Aminopyridine (AP) treatment effectively prevented neurons from STP-induced cell apoptosis, as indicated by increased cell survival and suppressed caspase-3 activity. Application of Ca-EDTA, a cell membrane-impermeable zinc chelator which can efficiently capture the synaptically released zinc, completely blocked the neuronal activity-dependent anti-apoptotic effect. Same results were also observed in cultured primary hippocampal neurons. Therefore, our results indicate that synaptic activity improves neuronal resistance to apoptosis via synaptically released zinc.